2011
DOI: 10.1016/j.ab.2010.09.040
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of metalloproteinase protein and activity profiling

Abstract: Proteolytic enzymes play fundamental roles in many biological processes. Members of the matrix metalloproteinase (MMP) family have been shown to take part in processes crucial in disease progression. The present study used the ExcelArray Human MMP/TIMP Array to quantify MMP and tissue inhibitor of metalloproteinase (TIMP) production in the lysates and media of 14 cancer and one normal cell line. The overall patterns were very similar in terms of which MMPs and TIMPs were secreted in the media versus associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…In vitro studies on skin cancer revealed that most melanoma cell lines, but not normal melanocytes, express MMP8 mRNA [57]. Yet at the protein level, MMP8 was only present in half of the nine melanoma cell lines examined by Giricz et al [115]. Similarly, MMP8 mRNA expression in keratinocytes of varying tumorigenic potential was detected in vitro but protein expression varied [116].…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies on skin cancer revealed that most melanoma cell lines, but not normal melanocytes, express MMP8 mRNA [57]. Yet at the protein level, MMP8 was only present in half of the nine melanoma cell lines examined by Giricz et al [115]. Similarly, MMP8 mRNA expression in keratinocytes of varying tumorigenic potential was detected in vitro but protein expression varied [116].…”
Section: Resultsmentioning
confidence: 99%
“…MMP‐3 activity was found to be significantly higher in synovial fluid from patients suffering from rheumatoid arthritis (RA) compared with control subjects. Our laboratory recently described an in situ MMP cell‐based assay with FRET peptide substrates in which no transfer of reagents is needed 19. MMP activity assays with three different FRET substrates were utilized to determine whether protein production correlated with function for melanoma WM‐266‐4 and fibroblast BJ cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Secreted MMPs are produced in inactive forms and must be activated extracellularly to perform their functions, which is then regulated by protease inhibitors. Therefore, activity assays may be more representative of the role of MMPs in pathogenic states than protein production analysis 48 . Thus, we quantitatively measured MMP activity using zymography in the current study.…”
Section: Discussionmentioning
confidence: 99%